Sarawak Regatta Festivals 2008 - Ahmad, Johanna Adlin (Universiti Teknologi MARA, Sarawak, 2009)
UiTM Sarawak successfully participated in two categories of the Sarawak Regatta 2008 held at the Waterfront, Kuching on the 2nd and 3rd August. The two categories were the boat decoration competition and also the boat race competition. Our participants came from the Faculty of Art and Design, the Hotour Club of the Faculty of Hotel and Tourism Management, and the Sports Unit from the Student’s Affair department.